On Some Inequalities of Uncertainty Principles Type in Quantum Calculus - Ahmed Fitouhi; Néji Bettaibi; Rym H. Bettaieb; Wafa Binous (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to generalize the 𝑞-Heisenberg uncertainty principles studied by Bettaibi et al. (2007), to state local uncertainty principles for the 𝑞-Fourier-cosine, the 𝑞-Fourier-sine, and the 𝑞-Bessel-Fourier transforms, then to provide an inequality of Heisenberg-Weyl-type for the 𝑞-Bessel-Fourier transform.